2014
DOI: 10.1371/journal.pone.0104702
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hospital-Acquired and Community-Onset Blood Stream Infections, South-East Austria

Abstract: PurposeThe objective of this study was to compare epidemiology, causative pathogens, outcome, and levels of laboratory markers of inflammation of community-onset (i.e. community-acquired and healthcare-associated) and hospital-acquired bloodstream infection (BSI) in South-East Austria.MethodsIn this prospective cohort study, 672 patients fulfilling criteria of systemic inflammatory response syndrome with positive peripheral blood cultures (277 community-onset [192 community-acquired, 85 healthcare-associated B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
3
31
0
2
Order By: Relevance
“…Patients with P. aeruginosa BSI, relative to those with non-P. aeruginosa BSI, more often had hospital-acquired BSI (51% versus 27%). Prior studies have demonstrated hospital-acquired infections to be associated with increased mortality (22)(23)(24). Although the overall effect of adding the "days to BSI" covariate on the P. aeruginosa BSI hazard ratio was small (Tables 4 and see Table S3 in the supplemental material), it is certainly possible that patients with hospital-acquired infections may have additional risks for poor outcome that were not fully accounted for in our multivariable Cox regression model.…”
Section: Thaden Et Almentioning
confidence: 98%
“…Patients with P. aeruginosa BSI, relative to those with non-P. aeruginosa BSI, more often had hospital-acquired BSI (51% versus 27%). Prior studies have demonstrated hospital-acquired infections to be associated with increased mortality (22)(23)(24). Although the overall effect of adding the "days to BSI" covariate on the P. aeruginosa BSI hazard ratio was small (Tables 4 and see Table S3 in the supplemental material), it is certainly possible that patients with hospital-acquired infections may have additional risks for poor outcome that were not fully accounted for in our multivariable Cox regression model.…”
Section: Thaden Et Almentioning
confidence: 98%
“…were about 3.3% of our all the BSI pathogens of our patients, of which candida was the predominant agent (Table 1). In a study that carried out by Hoenigl et al [20] in Austria, it was reported that no fungal pathogen was detected in community-acquired BSIs. Therefore, we thought that some of the hospitalized patients in immunosuppressive situation could re-admit to EC department in the study period.…”
Section: Discussionmentioning
confidence: 96%
“…(13.7%) and finally Pseudomonas aeruginosa (7.4%). A recent study on the characteristics of hospital-acquired and community-onset blood stream infections from Austria (Hoenigl et al, 2014), E. coli followed by Staphylococcus aureus were the most frequently isolated pathogens. This study has shown that, ESBL producing E. coli is an important cause of bloodstream infection presenting from bot h, the community and the hospit al settings (40.9 and 35.9%, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…The spread of communityacquired and hospital -acquired (nosocomial) bacteremia cause by E. coli imposes a major health burden. However, only few regional information is available on the differenc es between hospital-acquired and community acquired E. coli bacteremia (Hoenigl et al, 2014). Community and hospital spread of E. coli producing extended-spectrum beta-lactamases has increasingly been reported, most notably E. coli producing CTX-M strains (Woodford et al, 2004).…”
Section: Introductionmentioning
confidence: 99%